Endonuclease S1-sensitive site in chicken pro-alpha 2(I) collagen 5' flanking gene region. - Finer, M H (1984)
A site that is preferentially cleaved by the single-strand-specific endonuclease from Aspergillus oryzae was located in vitro 180 base pairs upstream from the 5' end of the chicken pro-alpha 2(I) collagen gene. It is found in supercoiled plasmids with a negative superhelical density of -0.024 or more but not in linear DNA molecules. The nuclease S1 sensitivity is retained in plasmids containing genomic fragments extending from position +8 to -285 (where +1 is the first transcribed base) and from -147 to -351 and also in a 5.7-kilobase EcoRI fragment that extends 1.6 kilobases 5' and 4.1 kilobases 3' to the 5' end of the gene. Analysis at the nucleotide level on a DNA sequence gel places the site at -181 to -182 on the sense strand and at -182 to -184 and -192 to -195 on the nonsense strand. These sites lie within a stretch of 42 pyrimidines interrupted by a single guanine and within the sequence T-C-C-C-T-C-C-C-T-T-C-C-T-C-C-C-T-C-C-C-T.